Method for producing laminated body
By using triazine-based silane coupling agent on a flexible circuit board, the base layer and molecular bonding layer are formed, and the adhesion between the metal layer and the resin is improved through electroless plating and electroplating technology, the adhesion under high temperature and high humidity environment is solved. The problems of insufficient and high cost achieve efficient bonding of metal layer and resin, which is suitable for high-frequency circuits.
Patent Information
- Application Number
- CN202280060970.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-12-24
- Filing Date
- 2022-12-21
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The existing flexible circuit boards have insufficient adhesion between the metal layer and the resin in high temperature and high humidity environments, and are relatively expensive, making it difficult to meet the needs of high-frequency circuits.
The base layer and the molecular bonding layer are formed by using triazine-based silane coupling agent. A smooth metal layer is formed on the resin substrate through electroless plating technology to improve the adhesion between the metal layer and the resin, and the metal layer is thickened by electroplating to Reduce costs.
In high temperature and high humidity environment, the adhesion between the metal layer and the resin is significantly improved, the cost is reduced, and the mechanical strength and transmission performance of the flexible circuit board are improved.
Smart Images

Figure CN117916083B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a laminate.
[0002] This application claims priority based on Japanese Patent Application No. 2021-211072 filed in Japan on December 24, 2021, and the contents of which are incorporated herein by reference. Background Art
[0003] Flexible circuit boards are used in mobile phones and other electronic products. As electronic products become smaller, more powerful, and have higher-speed communications, it is necessary to reduce the transmission loss of flexible circuit boards in high-frequency areas. Conductor loss is one of the main causes of transmission loss. In order to reduce conductor loss, wiring on smooth surfaces and high-precision circuits are being promoted.
[0004] As flexible circuit boards, polyimide resins with excellent bendability and heat resistance, copper foils with high conductivity, and copper-plated laminates are mostly used. As laminates of polyimide resins and copper foils, there are laminates formed by hot pressing copper foils and polyimide resins via thermoplastic polyimide resins, and cast materials formed by coating a varnish of a polyimide resin precursor on copper foil and thermally curing it. For laminates made by copper plating, electroless plating is performed on the surface of the polyimide resin, and then electroplating is performed.
[0005] However, although laminated materials and cast materials are low in cost, in order to ensure the adhesion between copper and resin substrate, the copper foil is roughened. Therefore, it is difficult to use laminated materials and cast materials for high-frequency circuits. In addition, in the case of copper plating, the surface of the copper-plated side of the polyimide resin is roughened by etching, etc. In this case, it is also difficult to use it for high-frequency circuits.
[0006] As a flexible wiring board whose copper foil surface is not roughened, Patent Document 1 discloses a flexible wiring board produced by allowing a catalyst to be supported on a molecular binder on the surface of a resin substrate and then performing electroless copper plating and electrolytic copper plating.
[0007] Patent document 2 discloses a flexible circuit board in which a chromium-containing adhesion enhancing layer, a nickel- or molybdenum-containing copper diffusion barrier layer, and a conductive layer composed of copper or a copper alloy are formed on one or both surfaces of a resin film containing a polyimide resin as a flexible circuit board in which the surface of the copper foil is not roughened.
[0008] Patent Document 3 discloses that electroless plating can be performed by attaching an amino group-containing alkoxysilane compound to the surface of a solid material without generating hydroxyl groups in a resin layer, heating the solid material, and then attaching a triazine thiol derivative and heating the solid material.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2007-17921
[0012] Patent Document 2: Japanese Patent Application Publication No. 2020-88123
[0013] Patent Document 3: Japanese Patent Application Publication No. 2010-280813 Summary of the invention
[0014] Problems to be solved by the invention
[0015] However, for the flexible circuit board disclosed in Patent Document 1, it is necessary to improve the adhesion between the metal layer and the resin in a high temperature and high humidity environment. In addition, in the case of the flexible circuit board disclosed in Patent Document 2, there is a problem that the cost of forming the adhesion enhancement layer and the copper diffusion barrier layer is high. Patent Document 3 shows that an amino-containing alkoxysilane compound is attached to the surface of a solid material and heated without causing the resin layer to generate hydroxyl groups, and then a triazine thiol derivative is attached and heated, so that electroless plating can be performed. However, what is needed now is that the adhesion between the resin and the metal in a high temperature and high humidity environment is higher than the method of Patent Document 3.
[0016] The present invention has been made in view of the above problems, and its object is to provide a method for producing a laminated body having a smooth surface of a metal layer on the side in contact with a resin, excellent adhesion between the metal layer and the resin under a high temperature and high humidity environment, and low cost.
[0017] Solutions to the Problem
[0018] In order to solve the above-mentioned problems, the present invention proposes the following means.
[0019] <1> One embodiment of the present invention relates to a method for producing a laminated body, the laminated body comprising a resin substrate and a metal layer provided on the resin substrate, the method comprising:
[0020] a step of forming a base layer by using a base triazine silane coupling agent represented by the following formula (1) on the surface of the resin substrate on which the metal layer is to be formed, directly or via another layer; and
[0021] The molecular bonding layer forming step forms a molecular bonding layer on the surface of the base layer using a catalyst-forming triazine-based silane coupling agent represented by the following formula (2).
[0022] [Chemistry 1]
[0023]
[0024] [Chemistry 2]
[0025]
[0026] [In formula (1), X 1 and X 2 is any one of 2-aminoethylamino, amino and azido, X 1 and X 2 Same or different from each other, R 1 , R 2 and R 3 represents a hydrogen atom or an alkoxy group, R 1 , R 2 and R 3 Same or different from each other, R 4 represents an alkylene group, R 5 represents a hydrogen atom, an alkyl group or an alkoxy group; in formula (2), X 3 and X 4 is a thiol group or a thiol metal salt, X 3 and X 4 Same or different from each other, R 6 , R 7 and R 8 represents a hydrogen atom or an alkoxy group, R 6 , R 7 and R 8 Same or different from each other, R 9 represents an alkylene group, R 10 represents a hydrogen atom, an alkyl group or an alkoxy group.]
[0027] <2> Above <1> The method for producing the laminate may further include a surface treatment step of introducing an oxygen-containing functional group or a nitrogen-containing functional group into the surface of the resin substrate.
[0028] <3> Above <2> In the method for producing a laminate, the surface treatment step may include a hydroxyl group modification step of introducing a hydroxyl group as an oxygen-containing functional group into the surface of the resin substrate.
[0029] <4> Above <3> In the method for manufacturing the laminate, the hydroxyl group modification step may be a corona treatment or oxygen gas introduction plasma.
[0030] <5> Above <2> In the method for producing a laminate, the surface treatment step may include an amino group modification step of introducing an amino group as a nitrogen-containing functional group into the surface of the resin substrate.
[0031] <6> Above <5> In the method for manufacturing the laminate, the amino group modification step may be a plasma treatment.
[0032] <7> Above <1> ~ <6> In any one of the methods for producing a laminate, the resin constituting the resin substrate may be one selected from the group consisting of epoxy resin, polyimide resin, polyphenylene sulfide, polytetrafluoroethylene, silicone rubber, cycloolefin polymer, polystyrene and liquid crystal polymer.
[0033] <8> Above <1> ~ <7> The method for producing a laminated body described in any one of the above may further include a catalyst supporting step of supporting a catalyst on the surface of the molecular bonding layer.
[0034] <9> Above <8> The method for producing the laminate may further include an electroless plating step of forming a metal layer by electroless plating on the surface of the molecular bonding layer carrying the catalyst.
[0035] <10> Above <9> The method for manufacturing a laminated body may further include an electroplating step of increasing the thickness of the metal layer by electroplating the metal layer formed in the electroless plating step.
[0036] Effects of the Invention
[0037] According to the above-mentioned embodiment of the present invention, an object is to provide a method for producing a laminated body having a smooth surface of a metal layer on the side in contact with a resin, excellent adhesion between the metal layer and the resin under a high temperature and high humidity environment, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 It is a cross-sectional schematic diagram of an embodiment of the present invention.
[0039] Figure 2 This is a flow chart of a method for producing a laminate according to one embodiment of the present invention. DETAILED DESCRIPTION
[0040] <Laminate>
[0041] As reasons for the decrease in the adhesion between the metal layer and the resin substrate under a high temperature and high humidity environment, the following can be cited: the metal element (e.g., copper) forming the metal layer diffuses in the resin substrate to decompose the resin, and the oxide of the metal layer is formed at the interface between the metal layer and the resin substrate, and peeling (protrusion) occurs between the metal layer and the oxide of the metal layer. In addition, as other reasons for the decrease in the adhesion between the metal layer and the resin substrate under a high temperature and high humidity environment, the barrier layer composed of an alkyl aminosilane coupling agent is destroyed due to hydrolysis, thereby reducing the barrier performance.
[0042] Therefore, the present inventors have conducted in-depth research on a method that can suppress the diffusion of metal elements in the metal layer into the resin substrate under a high temperature and high humidity environment at a low cost and suppress the generation of metal oxides formed at the interface between the metal layer and the resin substrate. As a result, by forming an intermediate layer (base layer) composed of a triazine silane coupling agent between the metal layer and the resin substrate, and then forming a molecular bonding layer with a triazine silane coupling agent that can support a catalyst, the adhesion between the metal layer and the resin under a high temperature and high humidity environment can be improved at a low cost. Based on the above insights, the present invention determines the various components of the laminate.
[0043] Hereinafter, a laminated body according to an embodiment of the present invention will be described with reference to the accompanying drawings. Figure 1 As shown, a laminate 100 according to an embodiment of the present invention includes a resin substrate 1, a base layer 2, a molecular bonding layer 3, and a metal layer 4. Each component will be described below.
[0044] (Resin base material)
[0045] The resin used as the resin substrate 1 is not particularly limited. The resin used as the resin substrate 1 is one or more selected from the group consisting of epoxy resin, polyimide resin (PI), polyphenylene sulfide (PPS), polytetrafluoroethylene (PTFE), silicone rubber, cycloolefin polymer (COP), polystyrene (PS) and liquid crystal polymer (LCP). These resins may be a single component, a copolymer, a mixture, or a laminate.
[0046] When the laminate 100 is used as a printed circuit board substrate, heat load is applied to the laminate 100 during soldering and wiring. In addition, when the laminate 100 is used for a movable part of an electronic product, sufficient mechanical strength is required. Therefore, polyimide resins, epoxy resins, liquid crystal polymers, etc. having excellent properties in terms of heat resistance, mechanical strength, and dimensional stability are preferred.
[0047] The resin of the resin base material 1 may contain inorganic particles such as talc, a lubricant, an antistatic agent, etc. for the purpose of improving mechanical strength.
[0048] The thickness of the resin substrate 1 is not particularly limited. For example, when the resin substrate 1 is used for a flexible circuit board, the thickness of the resin substrate 1 is preferably 1 μm or more and 200 μm or less. When the thickness of the resin substrate 1 is less than 1 μm, the mechanical strength of the resin substrate 1 may be insufficient, which is not preferred. The thickness of the resin substrate 1 is more preferably 3 μm or more. In addition, if the thickness of the film exceeds 200 μm, it is not preferred because the bending property may be reduced. The thickness of the resin substrate 1 is more preferably 150 μm or less.
[0049] The arithmetic mean roughness Ra of the resin substrate 1 is, for example, 0.01 μm to 1 μm. If the arithmetic mean roughness Ra is between 0.01 μm and 1 μm, it can also correspond to the miniaturization of the circuit. In addition, if the arithmetic mean roughness Ra is less than 0.2 μm, the transmission loss in the high-frequency region can be reduced. The arithmetic mean roughness Ra can be measured according to JIS B 0601:2013.
[0050] (Basal layer 2)
[0051] The base layer 2 is provided on the resin substrate 1, and contains a reactant of a triazine-based silane coupling agent for a base. Here, "provided on the resin substrate 1" includes not only providing the base layer 2 in contact with the surface of the resin substrate 1, but also providing an intermediate layer between the resin substrate 1 and the base layer 2. The reactant of the triazine-based silane coupling agent for a base is a compound formed by the reaction of the triazine-based silane coupling agent for a base. The base layer 2 may also contain impurities other than the reactant of the triazine-based silane coupling agent for a base.
[0052] The base layer 2 has a function of inhibiting the diffusion of the metal element of the metal layer 4 and the formation of metal oxides. The base layer 2 can be formed by, for example, forming a two-dimensional dense film by dehydration condensation of a base triazine silane coupling agent provided on the resin substrate 1. The base triazine silane coupling agent is represented by the following formula (1). In the following formula (1), X 1 and X 2 is any one of 2-aminoethylamino, amino and azido, X 1 and X 2 Same or different from each other, R 1 , R 2 and R 3 represents a hydrogen atom or an alkoxy group, R 1 , R 2 and R 3 Same or different from each other, R 4 represents an alkylene group, R 5 represents a hydrogen atom, an alkyl group or an alkoxy group.
[0053] By using a triazine silane coupling agent for a substrate represented by the following formula (1), the density of the film of the molecular bonding layer 3 provided on the substrate layer 2 is improved. Moreover, by using a triazine silane coupling agent for a substrate represented by the following formula (1), a dense structure can be formed. This dense structure can prevent the metal element and oxygen of the metal layer 4 from penetrating even in a high temperature and high humidity environment. As a result, the decrease in the adhesion between the resin substrate 1 and the metal layer 4 in a high temperature and high humidity environment can be suppressed. The substrate layer 2 is preferably bonded to the resin substrate 1 via a chemical bond. By bonding via a chemical bond, high adhesion can be obtained even if the resin substrate 1 is smooth.
[0054] [Chemistry 3]
[0055]
[0056] As R in the above formula (1) 1 , R 2 and R 3 Examples of the alkoxy group include methoxy, ethoxy, propoxy, isopropoxy, butoxy, and isobutoxy. 1 , R 2 and R 3 The alkoxy group is preferably a methoxy group or an ethoxy group.
[0057] As R in the above formula (1) 4 Examples of the alkylene group include methylene, ethylene, propylene, butylene, pentylene, hexylene and heptylene. 4 The alkylene group is preferably a propylene group.
[0058] As R in the above formula (1) 5 Examples of the alkyl group include methyl, ethyl, propyl and butyl groups.
[0059] As R in the above formula (1) 5 Examples of the alkoxy group include methoxy, ethoxy, propoxy, isopropoxy, butoxy and isobutoxy.
[0060] The thickness of the base layer 2 is not particularly limited as long as it covers the entire surface of the resin substrate 1. The thickness of the base layer 2, for example, can be greater than the thickness of a single molecule of the base triazine silane coupling agent constituting the base layer 2 (more than a monomolecular layer). When the thickness of the base layer 2 exceeds 400 nm, cracks may sometimes occur when bent, and the anti-permeation performance of the metal elements and oxygen of the metal layer 4 may be reduced. Therefore, the thickness of the base layer 2 is preferably less than 400 nm. The thickness of the base layer 2 is more preferably less than 200 nm.
[0061] (Molecular bonding layer)
[0062] The molecular bonding layer 3 is arranged on the base layer 2. Here, "arranged on the base layer 2" not only includes arranging the molecular bonding layer 3 in a manner in contact with the surface of the base layer 2, but also includes arranging an intermediate layer between the base layer 2 and the molecular bonding layer 3. By having the molecular bonding layer 3, it is easy to carry a catalyst as the core of electroless plating. The molecular bonding layer 3 is composed of an organic silicon compound having a triazine ring, and the triazine ring has a functional group having a catalyst-carrying function. As the functional group having a catalyst-carrying function, thiol groups, thiol metal salts, etc. can be cited. By having the function of carrying a catalyst, the adhesion between the molecular bonding layer 3 and the metal layer 4 can be improved. The molecular bonding layer 3 may also contain impurities other than the reactants of the triazine-based silane coupling agent.
[0063] The molecular bonding layer 3 contains a reactant of a triazine-based silane coupling agent for catalyst represented by the following formula (2). In the formula (2), X 3 and X 4 is a thiol group or a thiol metal salt, X 3 and X 4 Same or different from each other, R 6 , R 7 and R 8 represents a hydrogen atom or an alkoxy group, R 6 , R 7 and R 8 Same or different from each other, R 9 represents an alkylene group, R 10 Represents a hydrogen atom, an alkyl group or an alkoxy group. By using a triazine-based silane coupling agent for a catalyst represented by the following formula (2), the compactness of the molecular bonding layer 3 is improved, and it is easy to support the catalyst for forming the metal layer 4. In addition, by using a triazine-based silane coupling agent for a catalyst represented by the following formula (2), the adhesion with the base layer 2 is also improved.
[0064] [Chemistry 4]
[0065]
[0066] As R in the above formula (2) 6 , R 7 and R 8 Examples of the alkoxy group include methoxy, ethoxy, propoxy, isopropoxy, butoxy, and isobutoxy. 6 , R 7 and R 8 The alkoxy group is preferably a methoxy group or an ethoxy group.
[0067] As R in the above formula (2) 9 Examples of the alkylene group include methylene, ethylene, propylene, butylene, pentylene and heptylene. 9The alkylene group is preferably a propylene group.
[0068] As R in the above formula (1) 10 Examples of the alkyl group include methyl, ethyl, propyl and butyl groups.
[0069] As R in the above formula (1) 10 Examples of the alkoxy group include methoxy, ethoxy, propoxy, isopropoxy, butoxy and isobutoxy.
[0070] The thickness of the molecular bonding layer 3 is not particularly limited as long as it can support the catalyst to the extent that the metal layer 4 can be formed by electroless plating. The thickness of the molecular bonding layer 3 can be, for example, greater than the thickness of a single molecule of a triazine-based silane coupling agent for catalyst constituting the molecular bonding layer 3 (more than a monomolecular layer). When the thickness of the molecular bonding layer 3 exceeds 400nm, cracks may sometimes occur when bent, and the anti-permeation performance of the metal elements and oxygen of the metal layer 4 may be reduced. Therefore, the thickness of the molecular bonding layer 3 is preferably less than 400nm. The thickness of the molecular bonding layer 3 is more preferably less than 200nm.
[0071] (Metal layer)
[0072] The metal layer 4 is provided on the molecular bonding layer 3. Here, "provided on the molecular bonding layer 3" includes not only providing the metal layer 4 in contact with the surface of the molecular bonding layer 3, but also providing an intermediate layer between the molecular bonding layer 3 and the metal layer 4. Examples of the material of the metal layer 4 include nickel, gold, silver, tin, copper, and copper alloys. From the viewpoint of power loss and transmission loss, the metal constituting the metal layer 4 is preferably copper or a copper alloy having high electrical conductivity.
[0073] The thickness of the metal layer 4 is not particularly limited, but is, for example, 0.1 μm to 50 μm. The thickness of the metal layer 4 is more preferably 2 μm to 10 μm. When the thickness of the metal layer 4 is 0.1 μm to 50 μm, sufficient conductivity and mechanical strength can be obtained.
[0074] (Peel Strength)
[0075] After the laminate 100 was subjected to a HAST test (temperature 130°C, humidity 85% RH, 100 hours), when the peel strength between the resin substrate 1 and the metal layer 4 was measured at a tensile speed of 50 mm / min and a tensile angle of 90°, the peel strength between the resin substrate 1 and the metal layer 4 was 0.32 kN / m or more. If the peel strength between the resin substrate 1 and the metal layer 4 is 0.32 kN / m or more, the base layer 2 and the molecular bonding layer 3 have the function of preventing water vapor from passing through, and therefore it is preferred. In addition, after the laminate 100 was heated at 260°C for 5 minutes, when the peel strength was measured in the same manner, if the peel strength between the resin substrate 1 and the metal layer 4 is 0.50 kN / m or more, the base layer 2 and the molecular bonding layer 3 have the function of preventing the metal elements and oxygen of the metal layer 4 from passing through, and therefore it is preferred.
[0076] The above is a description of the laminate 100 of the present embodiment. In the laminate 100 of the present embodiment, although there is no intermediate layer between the resin substrate 1 and the base layer 2, an intermediate layer may be provided between the resin substrate 1 and the base layer 2. In the laminate 100 of the present embodiment, although there is no intermediate layer between the base layer 2 and the molecular bonding layer 3, a second intermediate layer may be provided between the base layer 21 and the molecular bonding layer 3.
[0077] <Method for producing laminate>
[0078] Next, a method for manufacturing the laminated body of this embodiment is described. Figure 2 As shown, the manufacturing method S100 of the laminated body of the present embodiment is a manufacturing method of the laminated body 100 having a resin substrate 1 and a metal layer 4 arranged on the resin substrate 1, and comprises: a surface treatment step S10, introducing an oxygen-containing functional group or a nitrogen-containing functional group into the resin substrate 1; a base layer forming step S11, forming a base layer on the surface of the resin substrate 1 on which the metal layer 4 is formed, directly or via other layers, using a base triazine-based silane coupling agent; a molecular bonding layer forming step S12, forming a molecular bonding layer 3 on the surface of the base layer 2 using a catalyst triazine-based silane coupling agent; a catalyst loading step S13, loading a catalyst on the surface of the molecular bonding layer 3; an electroless plating step S14, forming a metal layer 4 by electroless plating on the surface of the molecular bonding layer 3 loaded with the catalyst; and an electroplating step S15, thickening the metal layer 4 by electroplating the metal layer 4 formed in the electroless plating step S14. In addition, here, in the manufacturing method of this embodiment, "the metal layer 4 provided on the resin substrate 1" does not mean the metal layer provided directly on the resin substrate 1, but means the metal layer 4 provided above the resin substrate 1. In other words, it means a method for manufacturing a laminated body having a base layer 2 and a molecular bonding layer 3 between the resin substrate 1 and the metal layer 4.
[0079] (Surface treatment process)
[0080] In the surface treatment step S10, an oxygen-containing functional group or a nitrogen-containing functional group is introduced into the surface of the resin substrate 1 (the surface where the metal layer 4 is formed). Therefore, it is possible to easily form a base layer using a triazine-based silane coupling agent for a base. The surface treatment step S10 is not particularly limited as long as the oxygen-containing functional group or the nitrogen-containing functional group can be introduced into the surface of the resin substrate 1. For example, as oxygen-containing functional groups, hydroxyl groups, carbonyl groups, carboxyl groups, etc. can be cited. For example, as nitrogen-containing functional groups, amino groups, etc. can be cited. Hydroxyl groups or amino groups are preferred because they form chemical bonds with triazine-based silane coupling agents for bases, and high adhesion between the resin substrate 1 and the metal layer 4 can be obtained. The surface treatment step S10 preferably has a hydroxyl modification step for introducing hydroxyl groups as oxygen-containing functional groups or an amino modification step for introducing amino groups as nitrogen-containing functional groups. Here, the hydroxyl modification step for introducing hydroxyl groups into the surface of the resin substrate 1 is described as an example.
[0081] The hydroxyl modification process is, for example, corona discharge treatment or plasma treatment. By subjecting the resin substrate 1 to corona treatment or plasma treatment, hydroxyl groups can be introduced on the surface of the resin substrate 1. The amount of hydroxyl groups modified on the surface of the resin substrate 1 can be adjusted by treatment time, voltage, etc. Moreover, the gas used for plasma treatment is not particularly limited, and for example, oxygen (O2) and the like can be cited. Oxygen-introduced plasma is a plasma using oxygen. In addition, when ammonia (NH3) is used in plasma treatment, amino groups are introduced (ammonia-introduced plasma). This situation becomes an amino modification process.
[0082] (Base layer forming step)
[0083] In the base layer forming step S11, a base layer 2 is formed directly or via another layer on the surface of the resin substrate 1 treated in the surface treatment step S10 on which the metal layer 4 is to be formed, using a base triazine-based silane coupling agent. The silane coupling agent forming the base layer 2 is a base triazine-based silane coupling agent represented by the above formula (1).
[0084] Specific examples of the triazine-based silane coupling agent for the base of the above formula (1) include, for example, N,N'-bis(2-aminoethyl)-6-(3-triethoxysilylpropyl)amino-1,3,5-triazine-2,4-diamine (hereinafter sometimes referred to as aTES) represented by formula (3), 6-(3-triethoxysilylpropylamino)-1,3,5-triazine-2,4-diazide (hereinafter sometimes referred to as pTES) represented by formula (4), and the like.
[0085] [Chemistry 5]
[0086]
[0087] [Chemistry 6]
[0088]
[0089] The method for forming a layer using a triazine-based silane coupling agent for a base on the surface of the resin substrate 1 modified with an oxygen-containing functional group is not particularly limited. For example, a solution in which a triazine-based silane coupling agent for a base is dissolved (a triazine-based silane coupling agent solution for a base) may be applied to the resin substrate 1, or the resin substrate 1 may be immersed in the triazine-based silane coupling agent solution for a base. When the base layer 2 is formed at a monomolecular layer level, it is preferred to form the base layer 2 by immersing the resin substrate 1 in the triazine-based silane coupling agent solution for a base.
[0090] When immersed in the triazine silane coupling agent solution for substrate, the concentration of the triazine silane coupling agent solution for substrate is not particularly limited, but is, for example, 0.001 wt % to 10 wt %, the immersion time is, for example, 1 second to 60 minutes, and the immersion temperature is, for example, in the range of room temperature to 60° C.
[0091] The solvent used for the triazine silane coupling agent solution for substrate is not particularly limited as long as the triazine silane coupling agent for substrate is uniformly dissolved in the solvent. Examples of the solvent for the triazine silane coupling agent solution for substrate include water, ethanol, methanol, isopropanol, hexanone, hexane, acetone, and the like.
[0092] (Molecular bonding layer forming step)
[0093] In the molecular bonding layer forming step S12, a molecular bonding layer 3 is formed on the surface of the base layer 2 using a catalyst triazine-based silane coupling agent. The formation of the molecular bonding layer 3 improves the catalyst carrying capacity of the resin substrate 1. The silane coupling agent is a catalyst triazine-based silane coupling agent represented by the above formula (2).
[0094] Specific examples of the triazine-based silane coupling agent for catalyst of the formula (2) include (6-(3-triethoxysilylpropylamino)-1,3,5-triazine-2,4-dithiol monosodium salt (hereinafter sometimes referred to as nTES) represented by the following formula (5).
[0095] The method for forming the molecular bonding layer 3 using the triazine-based silane coupling agent for catalyst is not particularly limited. For example, a solution in which the triazine-based silane coupling agent for catalyst is dissolved (hereinafter sometimes referred to as the triazine-based silane coupling agent solution for catalyst) may be applied to the resin substrate 1 having the base layer 2 formed thereon, or the resin substrate 1 having the base layer 2 formed thereon may be immersed in the triazine-based silane coupling agent solution for catalyst. When the molecular bonding layer 3 is formed at the monomolecular layer level, it is preferred that the molecular bonding layer 3 is formed by immersing the resin substrate 1 having the base layer 2 formed thereon in the triazine-based silane coupling agent solution for catalyst.
[0096] [Chemistry 7]
[0097]
[0098] When immersed in the catalytic triazine silane coupling agent solution, the concentration of the catalytic triazine silane coupling agent is not particularly limited, but is, for example, 0.001 wt % to 2 wt %. The immersion time is, for example, 1 second to 60 minutes, and the immersion temperature is, for example, in the range of room temperature to 60°C.
[0099] The solvent used for the catalytic triazine silane coupling agent solution is not particularly limited as long as the catalytic triazine silane coupling agent is uniformly dissolved in the solvent. Examples of the solvent for the catalytic triazine silane coupling agent solution include water, ethanol, methanol, and the like.
[0100] (Catalyst Supporting Step)
[0101] In the catalyst loading step S13, the catalyst is loaded on the surface of the molecular bonding layer 3. The method for loading the catalyst is not particularly limited. As a method for loading the catalyst, there is a method of, for example, immersing the resin substrate 1 formed with the molecular bonding layer 3 in an aqueous solution containing a palladium salt, tin chloride, etc. By immersing the resin substrate 1 formed with the molecular bonding layer 3, the catalyst is loaded on the thiol group or the like contained in the triazine-based silane coupling agent for the catalyst.
[0102] Generally, palladium-tin (Pd-Sn) catalysts are used in the activation process, and the activation bath is prepared by dissolving PdCl2 and SnCl2·7H2O in water, for example. PdCl2 and SnCl2·7H2O are each adjusted in the concentration range of 0.001 mol / L to 1 mol / L, and are used in the temperature range of 0°C to 70°C and the immersion time is 1 second to 60 minutes.
[0103] (Electroless plating process)
[0104] In the electroless plating step S14, a metal layer 4 is formed on the surface of the molecular bonding layer 3 carrying the catalyst by electroless plating. Specifically, the metal layer 4 is formed on the molecular bonding layer 3 by immersing the resin substrate 1 carrying the catalyst in an electroless plating bath. Here, the electroless plating bath contains metal salts and reducing agents as main components, and auxiliary components such as pH adjusters, buffers, complexing agents, promoters, stabilizers, and improvers are added thereto. The supported catalyst and the triazine-based silane coupling agent are bonded by ionic bonds, so that the bonding strength is improved.
[0105] When the metal salt is copper, for example, it is CuSO4·5H2O. The metal salt concentration is 0.001 mol / L to 1 mol / L. In the case of nickel (Ni), the metal salt is, for example, NiSO4·6H2O (nickel sulfate) or NiCl2 (nickel chloride). In the case of silver (Ag), the metal salt is, for example, AgCN (silver cyanide). In the case of tin (Sn), the metal salt is, for example, SnSO4 (stannous sulfate). In the case of gold, the metal salt is, for example, K[Au(CN)2] (potassium gold cyanide).
[0106] The reducing agent refers to a substance that has the function of reducing the above-mentioned metal salt to generate a metal, and is KBH4, NaBH4, NaH2PO2, (CH3)2NH·BH3, CH2O, NH2NH2, hydroxylamine salt, N,N-ethylglycine, etc. The concentration of the reducing agent is 0.001 mol / L to 1 mol / L.
[0107] In order to improve the reduction efficiency of the electroless plating bath, for example, alkaline compounds, inorganic salts, organic acid salts, citrates, acetates, borates, carbonates, ammonium hydroxide, EDTA, diaminoethylene, sodium tartrate, ethylene glycol, thiourea, triazine thiol, triethanolamine, etc. can be added to the electroless plating bath.
[0108] The temperature of the electroless plating bath is, for example, in the range of 0° C. to 98° C., and the immersion time is, for example, in the range of 1 minute to 300 minutes.
[0109] (Electroplating process)
[0110] The electroplating step S15 performs electroplating on the metal layer 4 formed in the electroless plating step S14 to increase the thickness of the metal layer 4. The electroplating can be performed by a known method.
[0111] The above describes the manufacturing method S100 of the laminate of the present embodiment. In the manufacturing method S100 of the laminate of the present embodiment, although the surface treatment step S10 is provided, in the case where the surface of the resin substrate 1 (the surface forming the metal layer 4) is easy to form the base layer 2 using the base triazine silane coupling agent, the surface treatment step S10 may not be provided. Moreover, in the case where a base triazine silane coupling agent having a photoreactive functional group such as 6-(3-triethoxysilylpropylamino)-1,3,5-triazine-2,4-diazide is used as the base triazine silane coupling agent, a light irradiation step may be provided after the base layer forming step. After the base triazine silane coupling agent having an azide group is irradiated with light (e.g., ultraviolet light), a nitrogen alkene is generated from the azide group, and the generated nitrogen alkene reacts with the surface of the resin substrate 1 to obtain high adhesion. Furthermore, in the method for producing the laminated body of the present embodiment, the catalyst supporting step, the electroless plating step, and the electroplating step may be replaced by a metal vapor deposition step for forming a metal layer such as vacuum vapor deposition.
[0112] Example
[0113] Next, an embodiment of the present invention will be described, but the conditions of the embodiment are one condition example adopted to confirm the feasibility and effect of the present invention, and the present invention is not limited to this one condition example. The present invention can adopt various conditions as long as it does not deviate from the main purpose of the present invention and achieves the purpose of the present invention.
[0114] (Solution)
[0115] Each solution used in the preparation of Examples and Comparative Examples was prepared by the following method.
[0116] "3 wt% APTES solution"
[0117] 3 g of 3-aminopropyltriethoxysilane (APTES) manufactured by Tokyo Chemical Industry Co., Ltd. was added to 97 mL of distilled water while performing ultrasonic stirring for 10 minutes to prepare a 3 wt % APTES solution.
[0118] "0.5 wt% aTES solution"
[0119] 0.5 g of N,N'-bis(2-aminoethyl)-6-(3-triethoxysilylpropyl)amino-1,3,5-triazine-2,4-diamine (aTES) produced by Sulfur Chemical Research Institute was added to 99.5 mL of distilled water while ultrasonically stirring for 10 minutes to prepare a 0.5 wt% aTES solution.
[0120] "0.1wt% nTES solution"
[0121] 0.1 g of 6-(3-triethoxysilylpropylamino)-1,3,5-triazine-2,4-dithiol monosodium salt (nTES) produced by Sulfur Chemical Research Institute was added to 99.9 mL of distilled water while ultrasonically stirring for 10 minutes to prepare a 0.1 wt% nTES solution.
[0122] "Pre-soak solution"
[0123] 12.5 g of CATAPREP 404 manufactured by Rohm and Haas Electronic Materials was added to 50 mL of distilled water while performing ultrasonic stirring for 10 minutes to prepare a prepreg solution.
[0124] "Catalyst solution"
[0125] 12.5 g of CATAPREP 404 manufactured by Rohm and Haas Electronic Materials was added to 50 mL of distilled water while performing ultrasonic stirring for 10 minutes. After CATAPREP 404 was completely dissolved, 1.5 mL of CATAPOSIT 44 manufactured by Rohm and Haas Electronic Materials was added to prepare a catalyst solution.
[0126] "Accelerator Solution"
[0127] 2.5 g of ACCELERATOR 19E manufactured by Rohm and Haas Electronic Materials was added to 47.5 mL of distilled water while performing ultrasonic stirring for 10 minutes to prepare an accelerator solution.
[0128] 「Electroless plating solution」
[0129] In 42.6 mL of distilled water, 2.5 mL of ADOCOPPER IW-A manufactured by OKU CHEMICAL CO., LTD., 0.75 mL of ADOCOPPER C manufactured by OKU CHEMICAL CO., LTD., 4 mL of ADOCOPPER manufactured by OKU CHEMICAL CO., LTD., and 0.15 mL of electroless copper RN manufactured by OKU CHEMICAL CO., LTD. were added while ultrasonic stirring was performed for 10 minutes to prepare an electroless plating solution.
[0130] (Resin base material)
[0131] The polyimide substrate used was a polyimide substrate manufactured by Kinyosha Laboratory with a size of 50 mm×30 mm×130 μm in thickness. The LCP film used was an LCP film (30 mm×60 mm×50 μm in thickness) manufactured by Kuraray Co., Ltd.
[0132] (Plasma Treatment)
[0133] The resin substrate was soaked in ethanol, irradiated with ultrasound for 10 minutes, cleaned and dried. The surface of the dried resin substrate was plasma treated using a plasma treatment device (plasma etching machine made by Quei Semiconductor, external power: 100 W). The time recorded in the pretreatment column of Table 1 refers to the treatment time of the plasma treatment. In addition, O2 recorded in the pretreatment column refers to the gas used for the plasma treatment.
[0134] (Immersion conditions)
[0135] After pre-treating the resin substrate under the conditions described in Table 1, the resin substrate was immersed in an aTES solution or APTES solution of the concentration described in Table 1 for 1 minute and dried to form a base layer. In addition, when "None" is recorded in the pre-treatment column, the resin substrate was immersed in an aTES solution or APTES solution without pre-treatment. Thereafter, the resin substrate with the base layer formed was washed with water and dried. In the case where the concentration is recorded in the nTES column of Table 1, the resin substrate with the base layer formed was immersed in a 0.1wt% nTES solution for 5 minutes and then washed with distilled water. In addition, the "※" in the aTES column and the nTES column indicates a mixed solution of aTES and nTES. In Experiment No. 5, 0.5wt% aTES solution and 0.1wt% nTES solution were mixed, and the resin substrate was immersed in the mixed solution for 5 minutes. The mixed solution of Experiment No. 5 became colloidal and suspended.
[0136] (Metal layer formation conditions)
[0137] After cleaning, the resin substrates of Experiment No. 1 to Experiment No. 5 were immersed in the pre-impregnation solution for 1 minute, and then immersed in a catalyst solution at 50°C for 1 minute without washing after immersion, and then washed with distilled water. Then, without drying the resin substrate, it was immersed in the accelerator solution for 3 minutes and washed with distilled water. After washing, the resin substrate was immersed in an electroless copper plating solution at 32°C for 5 minutes in a wet state, washed with distilled water and ethanol, and dried. After drying, the resin substrate (laminate) with a copper layer formed was annealed at 80°C for 10 minutes. After annealing, it was cooled to room temperature. After cooling, the annealed laminate was immersed in a copper sulfate-based electroplating copper solution at a voltage of 15V and a current density of 0.02A / cm 2 Copper plating was performed for 90 minutes, followed by washing with distilled water and drying, and annealing was performed at 80° C. for 10 minutes to obtain laminates of Experiments No. 1 to No. 5. In Experiments No. 2 and No. 4, a base treatment step and a molecular bonding layer forming treatment step were performed.
[0138] (Determination of initial peel strength of coating)
[0139] The copper layer of the laminate of Experiment No. 1 to Experiment No. 5 was cut into a 1 cm wide incision, and a close tester (IMADA FORCE MEASUREMENT model mX2 made by IMADA) was used to measure the peel strength (plating initial peel strength) between the copper layer and the resin substrate under the conditions of a tensile speed of 50 mm / min and a tensile angle of 90 °. As long as the initial peel strength is more than 0.40 kN / m, there is no problem in actual use, so the initial peel strength is considered to be qualified as more than 0.40 kN / m. The results obtained are shown in Table 1.
[0140] (Determination of peel strength after HAST)
[0141] The laminates of Experiment No. 1 to Experiment No. 5 were placed in a constant temperature and humidity chamber at 130°C and 85% humidity for 100 hours, and a high-speed accelerated life treatment test (HAST) was performed. A 1 cm wide incision was cut in the copper layer of the laminate after the high-speed accelerated life treatment test, and a close-fitting tester (IMADA FORCE MEASUREMENT model mX2 manufactured by IMADA) was used to measure the peel strength between the copper layer and the resin substrate (peel strength after HAST) under the conditions of a tensile speed of 50 mm / min and a tensile angle of 90°. The results are shown in Table 1. As long as the peel strength after the HAST test is above 0.32 kN / m, there will be no problem in actual use, so the peel strength after the HAST test is above 0.32 kN / m, which is considered to be qualified. The results are shown in Table 1. In addition, for Experiment No. 5, the mixed solution of aTES and nTES became colloidal and suspended, and it was judged that a coarse precipitate was formed, so the HAST evaluation test was not performed.
[0142] (Determination of peel strength after heat resistance)
[0143] The laminates of Experiment No. 1 to Experiment No. 5 were subjected to a heat treatment at 260° C. for 5 minutes. A 1 cm wide incision was cut in the copper layer of the laminate after the heat treatment, and a close fit tester (IMADA FORCE MEASUREMENT model mX2 made by IMADA) was used to measure the peel strength (after heat-resistant peel strength) between the copper layer and the resin substrate at a tensile speed of 50 mm / min and a tensile angle of 90°. The peel strength was considered qualified when it was 0.40 kN / m or more. The results obtained are shown in Table 1.
[0144] [Table 1]
[0145]
[0146] Since the laminates of Experiment No. 2 and Experiment No. 4 have a base layer and a molecular bonding layer, the initial peel strength is 0.40 kN / m or more, the peel strength after the HAST test is 0.32 kN / m or more, and the peel strength after the heat treatment at 260° C. for 5 minutes is 0.40 kN / m or more. Therefore, the laminates of Experiment No. 2 and Experiment No. 4 have excellent heat resistance.
[0147] Industrial Applicability
[0148] According to the present invention, the surface of the metal layer in contact with the resin is smooth, the metal layer and the resin have excellent adhesion under a high temperature and high humidity environment, and the cost is low, so the industrial applicability is high.
[0149] Explanation of symbols
[0150] 1...Resin substrate
[0151] 2...basal layer
[0152] 3...Molecular bonding layer
[0153] 4...Metal layer
[0154] 100...Laminated body.
Claims
1. A method for producing a laminate comprising a resin substrate and a metal layer provided on the resin substrate, the method comprising: a step of forming a base layer by using a base triazine silane coupling agent represented by the following formula (1) on the surface of the resin substrate on which the metal layer is to be formed, directly or via another layer; and a molecular bonding layer forming step of forming a molecular bonding layer on the surface of the base layer using a triazine-based silane coupling agent represented by the following formula (2) as a catalyst, [Chemistry 1] [Chemistry 2] In formula (1), X 1 and X 2 is any one of 2-aminoethylamino, amino and azido, X 1 and X 2 Same or different from each other, R 1 , R 2 and R 3 represents a hydrogen atom or an alkoxy group, R 1 , R 2 and R 3 Same or different from each other, R 4 represents an alkylene group, R 5 represents a hydrogen atom, an alkyl group or an alkoxy group; in formula (2), X 3 and X 4 is a thiol group or a thiol metal salt, X 3 and X 4 Same or different from each other, R 6 , R 7 and R 8 represents a hydrogen atom or an alkoxy group, R 6 , R 7 and R 8 Same or different from each other, R 9 represents an alkylene group, R 10 represents a hydrogen atom, an alkyl group or an alkoxy group, The resin substrate has an arithmetic mean roughness Ra of 0.01 μm to 0.2 μm. 2 . The method for producing a laminate according to claim 1 , wherein in the molecular bonding layer forming step, the thickness of the molecular bonding layer is set to be not less than the thickness of a single molecule of a triazine-based silane coupling agent for catalyst constituting the molecular bonding layer and not more than 400 nm. 3 . The method for producing a laminate according to claim 1 , further comprising: a surface treatment step of introducing an oxygen-containing functional group or a nitrogen-containing functional group into the surface of the resin substrate on which the metal layer is formed.
4. The method for producing a laminate according to claim 3, wherein: The surface treatment step includes a hydroxyl group modification step of introducing a hydroxyl group as an oxygen-containing functional group into the surface of the resin substrate on which the metal layer is formed.
5. The method for producing a laminate according to claim 4, wherein: The hydroxyl modification step is a corona treatment or an oxygen gas plasma introduction step.
6. The method for producing a laminate according to claim 3, wherein: The surface treatment step includes an amino group modification step of introducing an amino group as a nitrogen-containing functional group into the surface of the resin substrate on which the metal layer is formed.
7. The method for producing a laminate according to claim 6, wherein: The amino group modification process is plasma treatment.
8. The method for producing a laminate according to claim 1, wherein: The resin constituting the resin substrate is one selected from the group consisting of epoxy resin, polyimide resin, polyphenylene sulfide, polytetrafluoroethylene, silicone rubber, cycloolefin polymer, polystyrene and liquid crystal polymer. 9 . The method for producing a laminate according to claim 1 , further comprising: a catalyst supporting step of supporting a catalyst on the surface of the molecular bonding layer. 10 . The method for producing a laminate according to claim 9 , further comprising: an electroless plating step of forming a metal layer by electroless plating on a surface of the molecular bonding layer carrying the catalyst. 11 . The method for producing a laminated body according to claim 10 , further comprising: an electroplating step of increasing the thickness of the metal layer by electroplating the metal layer formed in the electroless plating step.
Citation Information
Patent Citations
Method for forming reactive solid surface
JP2010280813A
Flexible substrate
JP2020088123A
Process for forming metal film, and product equipped with metal film
CN103038390A
Surface treatment method, surface treatment agent, and novel compound
CN104349848A
Laminated body, printed wiring board using same, flexible printed wiring board, and molded article
CN110753617A
